Agro physical features of gray soils in dry land that are exposed to erosion - Muratkasimov Alisher Sattarovich; Usmanov Umid Zakir Ogli (Zien Journals, 2023)
It is important to study the effect of erosion processes on the agro physical features of the soil in efficient use of dry land, preserving and enhancing fertility, higher yield and high-quality crops, application of different agrotechnology’s. This article describes a change of general physical features of typical gray soils in dry land under the influence of erosion processes.
Keywords: Typical gray soil; erosion; volume weight; specific weight